Microbial genomic traits and mineral protection jointly regulate the temperature sensitivity of soil carbon decomposition in boreal forests - Xinyi Zhang; Zhenglong Lu; Shuang Yin; Xuesen Pang; Yufan Liang; Zhenghu Zhou (Forest Ecosystems)
Soil organic carbon (SOC) decomposition in high-latitude boreal forests exhibits heightened sensitivity to climate change. However, a comprehensive understanding of the underlying drivers governing soil microbial decomposition responses to warming in these ecosystems remains elusive, especially regarding the roles of mineral protection and microbial genomic traits. In this study, we examined the temperature sensitivity (Q10) and minimum temperature (Tmin) of soil microbial respiration across a latitudinal gradient in China's boreal forests. The potential regulators, including climatic factors, soil physicochemical properties, substrate quality, mineral protection, and microbial genomic traits, were also synchronously measured. The results showed a positive correlation between Q10 and Tmin, i.e., greater microbial adaptability to low temperatures is associated with lower microbial sensitivity to increasing temperatures. Boreal forest soil with stronger mineral protection exhibited a higher Q10. In addition, microbial communities characterized by a higher abundance of coding genes demonstrated significantly lower Q10 and reduced Tmin. These results collectively highlight the pivotal roles of mineral protection and microbial genomic traits in shaping the biogeographic pattern of Q10 across boreal forests.